A Paradigm Shift in Flap Selection Protocols for Zones of the Lower Extremity using Perforator Flaps - Hallock, Geoffrey G. (Journal of Reconstructive Microsurgery, 2013)
Background Significant lower limb wounds often require soft tissue coverage using vascularized flaps. Traditionally, local muscles have been used for the proximal lower extremity and free flaps for the distal leg and foot, but perforator flaps over the past decade have been shown to be a reliable alternative.Methods The evolution of our lower limb flap selection for the period 1996 to 2000 was retrospectively compared with our current approach using perforator flaps. Flap selection was never random, but based according to wound location, severity, and flap availability.Results In the preperforator flap era, 101 of 122 (82.8%) flaps were muscle flaps. Over the last 5 years, this relative usage decreased to 36.4%, whereas perforator flaps were chosen almost half the time (49.6%). Local flaps still predominated as the choice for the proximal lower limb, and free flaps more distally, with perforator free flaps chosen twice as often as muscle flaps. Major complications occurred most commonly in the more distal lower extremity and were related to microsurgical catastrophes and not flap subtype.Conclusions Perforator flaps can be another soft tissue choice for all zones of the lower extremity, recognizing that function preservation is their major asset as no muscle need be included. Peninsular, propeller, or advancement perforator flaps proved to be valuable local nonmicrosurgical flap alternatives.
Keywords: perforator flaps; lower extremity zones; complex wound reconstruction